2021
DOI: 10.1590/fst.17920
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sensory attributes on overall liking by a gamma regression model: an analysis of Cerrado mixed fruits jams

Abstract: Factors that influence the acceptability and preferences of consumers have been perceived as sensory attributes, such as color, appearance, flavor, and texture. Understanding which attributes are most important for overall liking would be helpful to establish meaningful criteria for product grading. Thus, in addition to the overall chemical and sensory qualities, it is important to appreciate which sensory attributes make a product pleasant or unpleasant to a consumer. In this context, the aim of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…However, SCC and fruit firmness are affected by many factors, such as variety, growing conditions and precipitation, which will result in the uncertainty of maturity prediction. Taste is generally accepted as an indicator of fruit quality, which directly reflects the actual consumer preferences (Evrendilek, et al, 2016;Pereira et al, 2020). Le Lievre et al indicated that flavor components (starch, sugars and acids) in fruit affected the taste as perceived by consumers, which revealed the practicability of taste as an indicator of fruit quality (Le Lievre, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, SCC and fruit firmness are affected by many factors, such as variety, growing conditions and precipitation, which will result in the uncertainty of maturity prediction. Taste is generally accepted as an indicator of fruit quality, which directly reflects the actual consumer preferences (Evrendilek, et al, 2016;Pereira et al, 2020). Le Lievre et al indicated that flavor components (starch, sugars and acids) in fruit affected the taste as perceived by consumers, which revealed the practicability of taste as an indicator of fruit quality (Le Lievre, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A análise sensorial é um fator determinante para o desenvolvimento desse tipo de produto, uma vez que, a substituição do leite animal por matérias-primas vegetais pode influenciar na aceitabilidade e preferências dos consumidores quanto aos atributos de cor, aparência, sabor e textura (PEREIRA et al, 2021). Neste contexto, a avaliação e o estudo de mercado de produtos tipo queijo vegetal com diferentes bases vegetais e tecnologias de processo são fundamentais para o sucesso do produto.…”
Section: Introductionunclassified